Assessment of muscle strength in para-athletes: A systematic review of observational studies - O'Connor, S. R.; Fagher, K.; Williamson, S.; Pluim, B. M.; Ardern, C. L.; van Rensburg, D. C. J.; Heron, N. (Sports Medicine and Health Science, 2022)
Accurate and reliable evaluation of muscle strength in para-athletes is essential for monitoring the effectiveness of strength training and/or rehabilitation programmes, and sport classification. Our aim is to synthesise evidence related to assessing muscle strength in para-athletes. Four databases were searched from January 1990 to July 2021 for observational studies focusing on strength assessment. Independent screening, data extraction, and quality assessment were performed in duplicate. A total of 1764 potential studies were identified. Thirty met the inclusion criteria and were included in the review. The mean age of participants was 30.7 years (standard deviation [SD]: 2.4). The majority were men (88%) participating in wheelchair sports, including basketball, rugby, and tennis (23/30: 76%). Overall quality varied, with more than half of the studies failing to identify strategies for dealing with confounding variables. Despite manual muscle testing being a standard component of para-sport classification systems, evidence examining strength characteristics in para-athletes is derived primarily from isometric and isokinetic testing. In studies that included comparative strength data, findings were mixed. Some studies found strength values were similar to or lower than able-bodied athletic controls. However, an important observation was that others reported higher shoulder strength in para-athletes taking part in wheelchair sports than both able-bodied and disabled non-athletes. Studies need to develop accessible, standardised strength testing methods that account for training influence and establish normative strength values in para-athletes. There is also a need for additional studies that include female para-athletes and para-athletes with greater functional impairments.